THE POSITIVE EFFECT OF GREEN AGRICULTURE DEVELOPMENT ON ENVIRONMENTAL OPTIMIZATION - Shokhsuvor Yuldashevich Azizov; Abduraimov Otabek Sherali o'g'li (Scholar Express Journals, 2024)
Green development is a concept of sustainable development, aiming to protect the environment and ecosystems while meeting economic development needs.According to the study of the environmental impact of green agricultural development, this paper selects 12 basic indicators from the three dimensions of “ecological agriculture, green production, and output benefits” for the construction of China’s green agricultural development index. There are eight basic indicators used in the construction of the environmental index system, including the area of nature reserves and the level of environmental protection expenditures.
Keywords: environmental; ecological; construction